Clinical effects of the adjunctive use of polynucleotide and hyaluronic acid‐based gel in the subgingival re‐instrumentation of residual periodontal pockets: A randomized, split‐mouth clinical trial. Issue 3 (23rd November 2022) - Pilloni, Andrea; Rojas, Mariana A.; Trezza, Cinzia; Carere, Mauro; De Filippis, Alessandro; Marsala, Rosalia L.; Marini, Lorenzo
Abstract: Background: Polynucleotides (PN) and hyaluronic acid (HA) have been effective in stimulating the growth of primary gingival fibroblasts and promoting wound healing. The aim of this study was to investigate the clinical efficacy of a gel containing PN and HA used in association with subgingival re‐instrumentation in the treatment of residual periodontal pockets. Methods: Fifty patients were enrolled in a randomized, split‐mouth, single‐blind, clinical trial. For each patient, two teeth with similar residual pockets with probing depth (PD) ≥5 mm were selected to receive re‐instrumentation with (test group) or without (control group) the adjunctive use of a PN and HA‐based gel. Differences in changes of PD, gingival recession, clinical attachment level (CAL), modified sulcular bleeding index (mSBI), plaque index (PI) from baseline to 6, 8, 24, 36, and 48 weeks were analyzed and the frequencies of sites with PD ≤4 mm at 48 weeks were compared. Results: At 48 weeks, the test group showed better results in terms of PD reduction (2.08 ± 1.24 vs. 1.94 ± 1.19, p  = 0.533) and sites with PD ≤4 mm (38/50 vs. 35/50, p  = 0.499), although not statistically significant. Similarly, CAL gain was comparable between groups (test: 0.50 ± 1.85 vs. control: 0.36 ± 1.80, p  = 0.700). Significantly higher reduction in mSBI was recorded in the test group only in sites with baseline PD ≥6 mm ( p  = 0.004). Conclusions: The adjunctive use of a PN and HA‐based gel could help to ensure a greater reduction of clinical parameters of inflammation in deep residual pockets.